Lack of impact of the ALDH2 rs671 variant on breast cancer development in Japanese BRCA1/2‐mutation carriers. (7th November 2022) - Mori, Tomoharu; Okamoto, Yusuke; Mu, Anfeng; Ide, Yoshimi; Yoshimura, Akiyo; Senda, Noriko; Inagaki‐Kawata, Yukiko; Kawashima, Masahiro; Kitao, Hiroyuki; Tokunaga, Eriko; Miyoshi, Yasuo; Ohsumi, Shozo; et al.
Abstract: The aldehyde degrading function of the ALDH2 enzyme is impaired by Glu504Lys polymorphisms (rs671, termed A allele), which causes alcohol flushing in east Asians, and elevates the risk of esophageal cancer among habitual drinkers. Recent studies suggested that the ALDH2 variant may lead to higher levels of DNA damage caused by endogenously generated aldehydes. This can be a threat to genome stability and/or cell viability in a synthetic manner in DNA repair‐defective settings such as Fanconi anemia (FA). FA is an inherited bone marrow failure syndrome caused by defects in any one of so far identified 22 FANC genes including hereditary breast and ovarian cancer (HBOC) genes BRCA1 and BRCA2 . We have previously reported that the progression of FA phenotypes is accelerated with the ALDH2 rs671 genotype. Individuals with HBOC are heterozygously mutated in either BRCA1 or BRCA2, and the cancer‐initiating cells in these patients usually undergo loss of the wild‐type BRCA1/2 allele, leading to homologous recombination defects. Therefore, we hypothesized that the ALDH2 genotypes may impact breast cancer development in BRCA1/2 mutant carriers. We genotyped ALDH2 in 103 HBOC patients recruited from multiple cancer centers in Japan. However, we were not able to detect any significant differences in clinical stages, histopathological classification, or age at clinical diagnosis across the ALDH2 genotypes. Unlike the effects in hematopoietic cells of FA, our current data suggest that there is no impact of the loss of ALDH2 function in cancer initiation and development in breast epithelium of HBOC patients. Abstract : The common ALDH2 variant rs671 severely aggravates DNA repair‐deficient disorder Fanconi anemia, and it is expected that breast cancer developed in BRCA1/2 mutation carriers are similarly affected. Now we elucidated this is not the case in the actual patient cohort, highlighting cell type‐specific differences in the protection/detoxification mediated by ALDH2.